Mencari Ulama Pewaris Nabi Ulama Akherat Pewaris Nabi, Ulama Dunia Pewaris Qarun - Aqis Bil Qisthi (Bintang Usaha Jaya, 2005)
Mencari Ulama Pewaris Nabi Ulama Akherat Pewaris Nabi, Ulama Dunia Pewaris Qarun